2011
DOI: 10.1007/s13225-011-0123-z
|View full text |Cite
|
Sign up to set email alerts
|

Goodbye morphology? A paradigm shift in the delimitation of species in lichenized fungi

Abstract: Accurate species delimitations are crucial for ecological and conservation studies, assessments of biotic diversity, and identifying factors driving diversification. Estimates suggest that the vast majority of fungal species are currently unknown. Although many undescribed fungal taxa are expected to be indentified within understudied groups and from underexplored areas, mounting evidence suggests a substantial number of unrecognized fungal species are likely hidden within traditional phenotypebased species in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
147
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 175 publications
(155 citation statements)
references
References 152 publications
8
147
0
Order By: Relevance
“…In general, it has been shown that in some lichen genera the presence of soredia is a poor diagnostic character (Tehler et al 2004(Tehler et al , 2009Ferencova et al 2010;Lumbsch & Leavitt 2011). …”
Section: Discussionmentioning
confidence: 99%
“…In general, it has been shown that in some lichen genera the presence of soredia is a poor diagnostic character (Tehler et al 2004(Tehler et al , 2009Ferencova et al 2010;Lumbsch & Leavitt 2011). …”
Section: Discussionmentioning
confidence: 99%
“…This phylogenetic tree-informed approach to assessing species boundaries represents a common practice in studies of lichen-forming fungi. Previously unrecognized species-level clades with corresponding subtle, or overlooked, phenotypic characters have been commonly observed in both crustose lichens [e.g., Acarospraceae (Wedin et al 2009), Graphidaceae (Rivas Plata andLumbsch 2011;Papong et al 2009), Lecanoraceae (Leavitt et al 2011a), Lecideaceae (Ruprecht et al 2010), Mycoblastaceae , and Teloschistaceae (Vondrák et al 2009;Muggia et al 2008)] and foliose and fruticose lichens [e.g., Lobariaceae (Moncada et al 2014;McDonald et al 2003), Parmeliaceae (Leavitt et al 2013a;Wirtz et al 2012;Divakar et al 2005;Molina et al 2004;Kroken and Taylor 2001), Peltigeraceae (O'Brien et al 2009;Goffinet et al 2003), Physciaceae Divakar et al 2007), and Sphaerophoraceae (Högnabba and Wedin 2003)]. As a specific example, Lücking et al (2008) used a combination of medullary chemistry and underside pigmentation in specimens from the Heterodermia obscurata group in Costa Rica to corroborate monophyletic clades in an ITS gene tree as species-level lineages.…”
Section: 3mentioning
confidence: 99%
“…The use of chemistry in lichen taxonomy has been discussed in detail in numerous reviews (Lumbsch 1998a, b;Rogers 1989;Brodo 1986;Egan 1986;Leuckert 1985;Brodo 1978;Hawksworth 1976;Culberson 1969Culberson , 1970), and we refer readers to these valuable sources for a more comprehensive perspective on lichen chemistry. In short, extrolites (secondary metabolites) belong to various classes; the most common and diverse include depsides, depsidones, chlorinated xanthones, and anthraquinones (Lumbsch 2002;Culberson 1969). The presence or absence of specific extrolites, or their replacements by another substance, is widely used to distinguish species, particularly when correlated with differences in geographic distributions.…”
Section: Selecting the Appropriate Datamentioning
confidence: 99%
“…Indeed, recent phylogenetic studies suggest high amounts of homoplasy in phenotypical characters used to delimit taxa in lichenized fungi (Grube et al 2004;Tehler and Irestedt 2007;Schmitt et al 2009;Rivas Plata and Lumbsch 2011;Lumbsch et al 2014a). Hence, molecular data have greatly increased our ability to identify distinct lineages, including the detection of numerous cryptic lineages (Crespo and Lumbsch 2010;Lumbsch and Leavitt 2011;Leavitt et al 2015). While numerous foliose and fruticose lichen groups have been studied in some detail, especially in the diverse Parmeliaceae, our knowledge on species delimitation in crustose lichens is still in its infancy.…”
Section: Introductionmentioning
confidence: 99%